Collaborative Learning, Self-Regulated Learning, and English Communication Competence Among Students in Islamic Higher Education - Rijnan (Formad English Foundation NTB Jakarta, 2026)
English communication competence has become an essential competency for students in Islamic Higher Education, yet many learners continue to experience difficulties in developing effective communicative abilities despite growing interest in learner-centered English language instruction. This study aimed to systematically synthesize recent empirical evidence concerning collaborative learning, self-regulated learning, and English communication competence, examine the relationships among these three constructs, and identify current research gaps and future research directions within Islamic Higher Education. The study employed a Systematic Literature Review (SLR) following the PRISMA 2020 framework. Peer-reviewed journal articles published between 2021 and 2026 were retrieved from major academic databases using predefined search strategies and explicit inclusion and exclusion criteria. The selected studies were analyzed through thematic synthesis to identify recurring themes, methodological characteristics, conceptual developments, and empirical findings. The review revealed a substantial increase in research on collaborative learning, self-regulated learning, and English communication competence, with recent studies emphasizing learner-centered, technology-enhanced, and communication-oriented pedagogies. The findings consistently demonstrated that collaborative learning promotes authentic interaction, peer engagement, and communicative practice, whereas self-regulated learning strengthens learner autonomy, motivation, strategic learning, and self-monitoring. Their integration was found to enhance English communication competence, including speaking performance, communicative confidence, intercultural awareness, and digital communication skills. However, studies integrating these three constructs within Islamic Higher Education remain limited. Overall, this review provides an integrated conceptual framework that contributes to English language education theory while offering practical guidance for lecturers, curriculum developers, and researchers in designing learner-centered and technology-supported instructional practices that strengthen English communication competence in Islamic Higher Education.